PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA INTERAKTIF MENGGUNAKAN ADOBE FLASH CS 5 POKOK BAHASAN TRIGONOMETRI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS X SMA - Nuryadi, Nuryadi; Bahtiar, Zulfa Hanani (AlphaMath : Journal of Mathematics Education, 2017)
This research aims at 1) developing interactive media for mathematics learning by usingAdobe Flash CS 5 in trigonometry material to enhance students’ learning motivation; 2)recognizing the media quality through validity, practicality, and effectiveness. The used ofresearch design is research and development (R&D) which adapted the steps from Borg andGall. These steps consist of three steps as introduction, development, and validation. Thisresearch shows that the applied media is useable which assessed through aspect of validity,practicality, and effectiveness of interactive learning media.Keywords: Adobe Flash CS 5, learning motivation, mathematics learning media